The Performance Practice of Electroacoustic Music The Studio di Fonologia years - Toro-Pérez, Germán (Zuercher Musikstudien, 2018)
This book is dedicated to the topic of performance practice of electroacoustic music, focusing mainly on the production of RAI's Studio di Fonologia in Milan between the 1950s and 1970s. It is the result of an in-depth dialogue between musicology and musical practice, presenting musicological and practice-based contributions, some dealing with specific problems of performance practice, in particular the analysis and interpretation of the aesthetic prerequisites and production conditions of the repertoire from a musicological perspective, others focusing on specific works and on their realisation from a performer's perspective. Overall, this publication is intended as a contribution to the performance culture of the repertoire.